Intestinal organoids: The path towards clinical application - Hady Yuki Sugihara; Ryuichi Okamoto; Tomohiro Mizutani (European Journal of Cell Biology)
Organoids have revolutionized the whole field of biology with their ability to model complex three-dimensional human organs in vitro. Intestinal organoids were especially consequential as the first successful long-term culture of intestinal stem cells, which raised hopes for translational medical applications. Despite significant contributions to basic research, challenges remain to develop intestinal organoids into clinical tools for diagnosis, prognosis, and therapy. In this review, we outline the current state of translational research involving adult stem cell and pluripotent stem cell derived intestinal organoids, highlighting the advances and limitations in disease modeling, drug-screening, personalized medicine, and stem cell therapy. Preclinical studies have demonstrated a remarkable functional recapitulation of infectious and genetic diseases, and there is mounting evidence for the reliability of intestinal organoids as a patient-specific avatar. Breakthroughs now allow the generation of structurally and cellularly complex intestinal models to better capture a wider range of intestinal pathophysiology. As the field develops and evolves, there is a need for standardized frameworks for generation, culture, storage, and analysis of intestinal organoids to ensure reproducibility, comparability, and interpretability of these preclinical and clinical studies to ultimately enable clinical translation.